2016
DOI: 10.1002/ar.23376
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal differentiation in the developing human spinal ganglia

Abstract: The spatiotemporal developmental pattern of the neural crest cells differentiation toward the first appearance of the neuronal subtypes was investigated in developing human spinal ganglia (SG) between the fifth and tenth developmental week using immunohistochemistry and immunofluorescence methods. First neurofilament-200-(NF200, likely myelinated mechanoreceptors) and isolectin-B4-positive neurons (likely unmyelinated nociceptors) appeared already in the 5/6th developmental week and their number subsequently i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 65 publications
4
12
0
Order By: Relevance
“…Since the myelinization still does not occur in the presented investigated periods, NF200 positive fibers could be described as nonnociceptive ones. The same was found in developing human spinal ganglia (Vukojevic et al, 2016) and in the SC (Foster et al, 1987). Moreover, NF200 was expressed in mechanoreceptors of dural afferents in mouse, pointing that all trigeminal ganglion neurons expressing NF200 innervate mouse dura (Ren et al, 2018).…”
Section: Discussionsupporting
confidence: 73%
See 4 more Smart Citations
“…Since the myelinization still does not occur in the presented investigated periods, NF200 positive fibers could be described as nonnociceptive ones. The same was found in developing human spinal ganglia (Vukojevic et al, 2016) and in the SC (Foster et al, 1987). Moreover, NF200 was expressed in mechanoreceptors of dural afferents in mouse, pointing that all trigeminal ganglion neurons expressing NF200 innervate mouse dura (Ren et al, 2018).…”
Section: Discussionsupporting
confidence: 73%
“…In the present study CGRP was expressed in all three SC zones, especially during the 5th–6th DW indicating cessation of the neural differentiation into sensory neurons. Our previous study on SG has also shown that first signs of the CGRP appeared in the sixth week of development (Vukojevic et al, 2016), confirming that the fibers which terminate in the superficial laminae of the dorsal SC are from neurons located in the DGR (Ribeiro da Silva, 1995; Ribeiro da Silva and De Koninck, 2008). These small peptidergic afferents are associated to the transmission of the pain related informations.…”
Section: Discussionsupporting
confidence: 61%
See 3 more Smart Citations